2014
DOI: 10.22146/gamaijb.5658
|View full text |Cite
|
Sign up to set email alerts
|

The Market Quality to Technical Analysis Performance: Intercountry Analysis

Abstract: Abstract:The main objective of this research is to discuss the impact of market quality on technical analysis profitability using inter-country analysis. Market quality is proxied by market capitalization. Technical analysis performance (profitability) is calculated using technical analysis return for MA5 indicator and short transaction strategy. This study uses the OSIRIS and Yahoo Finance databases. Using 21 countries with 50 companies for each country, this study finds that market quality affects technical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The study [7] has identified the random forest classifier as the most accurate and consistent classifier where its ensemble was instrumental in achieving a higher level of accuracy. The study done by [4] has focused on analyzing the market quality's impact on the profitability of technical analysis with the special case of inter-country data. The study [4] confirmed that market quality which was measured as market capitalization was affecting the performance of technical analysis based on data of 50 companies selected across from 21 countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The study [7] has identified the random forest classifier as the most accurate and consistent classifier where its ensemble was instrumental in achieving a higher level of accuracy. The study done by [4] has focused on analyzing the market quality's impact on the profitability of technical analysis with the special case of inter-country data. The study [4] confirmed that market quality which was measured as market capitalization was affecting the performance of technical analysis based on data of 50 companies selected across from 21 countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study done by [4] has focused on analyzing the market quality's impact on the profitability of technical analysis with the special case of inter-country data. The study [4] confirmed that market quality which was measured as market capitalization was affecting the performance of technical analysis based on data of 50 companies selected across from 21 countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Developed markets and emerging markets have different characteristics. The study of Hartono and Sulistiawan (2014) presents the evidence that stock market in emerging countries, including Indonesia are less efficient compare to those in developed market, and hence, behavioural finance theory is more able to explain the behaviour of investors. By presenting evidence from emerging markets, this study provides comparative picture from different markets (Rahman and Mustafa, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The first reason, technical analysis tends to produce better performance in developing market than that in developed market (Fifield et al 2005;McKenzie 2007;Hartono and Sulistiawan, 2014). The second, technical analysis is competing information to fundamental information, including accounting information (Franchis et al 2002;Flanegin and Rudd 2005;.…”
Section: Introductionmentioning
confidence: 99%